أبناؤنا ومخاطر الشاشات - قديري مصطفى (University of Eloued جامعة الوادي, 2024)
ملخص: نهدف من خلال هذه المداخلة الى اعادة مسائلة بعض المشكلات الكلاسيكية المرتبطة بتأثيرات الشاشة على الاطفال، خاصة في الوقت الذي نعيش فيه حيث سيطرت مختلف الاجهزة الالكترونية على أوقاتنا واصبحت جزءا من حياتنا، وبالرغم من الفوائد التي تقدمها الاجهزة الالكترونية خاصة من الناحية المعرفية والتعليمية ، الا ان المخاطر اصبحت مؤكدة بين تعريض الاطفال الصغار الاقل من سنتين للشاشات، وظهور مشكلات تأخر اللغة و المشكلات السلوكية والادراكية و أعرض التوحد ...الخ، وهو ما سنحاول توضيحه في هذه المداخلة من خلال تقديم عرض لتأثيرات الشاشة على الاطفال الصغار والتي من شانها يمكننا ان نعتبر ان مشاهدة الاطفال للشاشة والبرامج في عمر اقل من سنتين قد يعتبر حقا جريمة في حق الطفل.Abstract : Through this intervention, we aim to reconsider some classical issues related to the effects of screen time on children, especially in the current era where various electronic devices dominate our time and have become part of our lives. Despite the benefits offered by electronic devices, particularly in terms of cognitive and educational aspects, the risks are becoming evident, especially when exposing children under the age of two to screens. This exposure has been linked to issues such as language delays, behavioral and cognitive problems, and even autism spectrum disorder. We will attempt to clarify these issues by presenting an overview of the effects of screen time on young children, suggesting that allowing children under the age of two to watch screens and programs may indeed be considered a crime against the child
قراءة في الواقع وعرض للأدبيات
Keywords: الطفل; الشاشة; طفل الشاشة; Child; Screen; Screen Time Child